Scaling up the curvature of mammalian metabolism - Bueno, Juan; López-Urrutia, Ángel (Frontiers in Ecology and Evolution, 2014)
A curvilinear relationship between mammalian metabolic rate and body size on a log-log scale has been adopted in lieu of the longstanding concept of a 3/4 allometric relationship (Kolokotrones et al. 2010). The central tenet of Metabolic Ecology (ME) states that metabolism at the individual level scales-up to drive the ecology of populations, communities and ecosystems. If this tenet is correct, the curvature of metabolism should be perceived in other ecological traits. By analyzing the size scaling allometry of eight different mammalian traits including basal and field metabolic rate, offspring biomass production, ingestion rate, costs of locomotion, life span, population growth rate and population density we show that the curvature affects most ecological rates and